Divorcio litigioso y la prelación de los curadores en base de la decisión del Juez - Gaibor Piza, Javier Manuel (2020)
The following research is focused on studying the priority of decision-making by the judge when choosing ad-litem guardians within the disputed divorce, conducted within the summary procedure. The scope of the investigation will start from the Organic Code of Childhood and Adolescence, and will be extended within supplementary norms such as the Civil Code and General Organic Code of Processes because the existing problem concerns the suitability of the ad-litem curator. The guardian ad-litem has the function of representing and protecting the minor, since he has not reached the age of majority and is incapable of being able to represent himself before the law; In other words, after the litigious divorce trial, one of the parents is not in the condition to provide the required attention to the minor, the role of the appointed guardians must be executed in accordance with the resolution issued by the judge and they must ensure education , security essentially exercise everything concerning the best interests of the minor...............